Detection of synergistic combinations of Baccharis extracts with Terbinafine against Trichophyton rubrum with high throughput screening synergy assay (HTSS) followed by 3D graphs. Behavior of some of their components - Rodriguez, María Victoria (2013)
Forty four extracts from nine Baccharis spp. from the Caulopterae section were tested in combination with terbinafine against Trichophyton rubrum with the HTSS assay at six different ratios with the aim of detecting those mixtures that produced a ≥50%statistically significant enhancement of growth inhibition. Since an enhanced effect of a combination respective of its components, does not necessarily indicate synergism, three-dimensional (3D) dose–response surfaces were constructed for each selected pair of extract/antifungal drug with the aid of CombiTool software. Ten extracts showed synergistic or additive combinations which constitutes a 22% hit rate of the extracts submitted to evaluation. Four flavonoids and three ent-clerodanes were detected in the active Baccharis extracts with HPLC/UV/ESI-MS methodology, all of which were tested in combination with terbinafine. Results showed that ent-clerodanes but not flavonoids showed synergistic or additive effects. Among them, bacchotricuneatin A followed by bacrispine showed synergistic effects while hawtriwaic acid showed additive effects.